The Little Red Train - Sommer, Carl, 1930-; James, Kennon (Houston, Tex. : Advance Pub., 2000)
When the three big trains refuse to go up the mountain in the deep snow, the Little Red Train finds brave helpers and goes on a rescue mission to take food to the stranded villagers.
Keywords: Railroad trains -- Fiction; Perseverance (Ethics) -- Fiction